Application of damage control surgery in patients with sacrococcygeal deep decubitus ulcers complicated by sepsis. Issue 10 (October 2021) - Wei, Zhiyi; Zhu, Jingfa; Lin, Tianlai; Cai, Hehui; Fang, Xiangjian; Zhu, Yixin; Yang, Xiaolan; Cheng, Juntao
Objective: To evaluate the clinical application of damage control surgery (DCS) in patients with sacrococcygeal deep decubitus ulcers complicated by sepsis. Methods: We conducted a 3-year retrospective clinical study of 32 patients with deep sacrococcygeal bedsores and sepsis admitted from January 2018 to January 2021. According to the concept of DCS, the wound was temporarily closed with vacuum sealing drainage after primary debridement, and a local rhomboid flap was designed to repair the wound in the second stage. Finally, the clinical therapeutic effect was observed. Results: Twenty-nine patients were treated with skin flap translocation and were cured clinically. Specifically, the skin flap survived in 27 of the 29 patients after the first translocation attempt (success rate of 93.1%). One patient developed incisional dehiscence, and one patient developed a hydrocele under the skin flap. Conclusions: Application of DCS in patients with sacrococcygeal deep decubitus ulcers complicated by sepsis improves the therapeutic success rate and reduces the risks of the operation and complication rate. It has unique advantages and is worthy of clinical promotion.